Hybrid Practices in Moving Image Design Methods of Heritage and Digital Production in Motion Graphics - Macdonald, Iain.; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book, written from the perspective of a designer and educator, brings to the attention of media historians, fellow practitioners and students the innovative practices of leading moving image designers. Moving image design, whether viewed as television and movie title sequences, movie visual effects, animating infographics, branding and advertising, or as an artform, is being increasingly recognised as an important dynamic part of contemporary culture. For many practitioners this has been long overdue. Central to these designers' practice is the hydridisation of digital and heritage methods. Using interviews with world-leading motion graphic designers, Oscar-nominated visual effects supervisors and moving image artists this book examines hybrid moving image that re-invigorate heritage practices, the handmade and the analogue crafts. Now is the time to ensure that heritage skills do not atrophy, but that their qualities and provenance are understood as potent components with digital practices in new hybrids. Iain Macdonald is Associate Professor, Subject Group Leader of Design, Photography and Advertising, and Programme Leader for MSc Creative Advertising at Edinburgh Napier University, UK. His creative industry experience spans over 25 years as an award winning television graphic designer at BBC Television, and as a film and commercials director. .
Introduction -- PART ONE.HYBRID MOTION: past, present and future -- 1.Heritage and Digital -- 2.Skills and Educational Research -- 3.Hybrid futures in Art & Design Education -- 4.Political Economy: Conditions of Production -- PART TWO.NARRATIVES OF PRODUCTION -- 5.Graham McCallum, executive creative director of Kemistry -- 6.No Brain, directors and animators -- 7.Richard Stammers, Visual Effects Supervisor -- 8.Adam Valdez, Visual Effects Supervisor -- 9.Eric Dyer, moving image artist -- 10.Momoco, motion graphic designers -- Conclusion. .
Keywords: Fine Arts; Motion pictures; Animated films; Architectural design; Computer science; Media Design; Image Processing and Computer Vision